Mecanismos de absorção de aminoácidos e oligopeptídios. Controle e implicações na dietoterapia humana - Frenhani, Patrícia Baston; Burini, Roberto Carlos [UNESP] (FapUNIFESP (SciELO), 1999)
The mechanisms involved in the absorption of amino acids and oligopeptides are reviewed regarding their implications in human feedings. Brush border and basolateral membranes are crossed by amino acids and di-tripeptides by passive (facilitated or simple diffusion) or active (Na + or H + co-transporters) pathways. Active Na +-dependent system occurs mainly at brush border and simple diffusion at basolateral, both membranes have the passive facilitated transport. Free-amino acids use either passive or active transport systems whereas di-tripeptides do mainly active (H + co-transporter). Brush border have distinctive transport system for amino acids and di-tripeptides. The former occurs mainly by active Na + dependency whereas the later is active H +-dependent with little affinity for tetra or higher peptides. Free amino acids are transported at different speed by saturable, competitive carriers with specificity for basic, acidic or neutral amino acids. Di and tripeptides have at least two carriers both electrogenic and H +-dependent. The basolateral membrane transport of amino acids is mostly by facilitated diffusion while for di-tripeptides it is an active anion exchange associated process. The main regulation of amino acids and di-tripeptide transport is the presence o substrate at the mucosal membrane with higher the substrate higher the absorption. Di and tripeptides are more efficiently absorbed than free amino acids which in turns are better absorbed than oligopeptides. So di-tripeptides result in better N-retention and is particularly useful in cases of lower intestinal absorption capacity. The non-absorbed peptides are digested and fermented by colonic bacteria resulting short-chain fatty acids, dicarboxylic acids, phenolic compounds and ammonia. Short-chain fatty acid provides energy for colonocytes and bacteria and the ammonia not fixed by bacteria returns to the liver for ureagenesis.
Mechanisms of amino acids and oligopeptides absorption in humans
Keywords: Diet; Intestinal absorption; Metabolism; Peptides; Proteins; amino acid; carrier protein; oligopeptide; peptide; basement membrane; human; intestine absorption; metabolism; physiology; protein intake; review; Amino Acids; Basement Membrane; Carrier Proteins; Dietary Proteins; Humans; Intestinal Absorption; Oligopeptides